Bacteremia and central line infection caused by Bosea thiooxidans. (2020) - Skipper, Caleb; Ferrieri, Patricia; Cavert, Winston
Abstract: We describe a case of central venous catheter infection and bacteremia caused by Bosea thiooxidans, which has not been previously described in the literature. Bosea spp. is a gram-negative bacterium that has been isolated from hospital water supplies and may become an important cause of nosocomial infections.